Analisis Pengaruh Sikap, Norma Subjektif, Kontrol Perilaku, dan Kemaslahatan Terhadap Perilaku Mengonsumsi Makanan Halal - Annisa Maulidia Alfian; Nurul Huda; Alfian Alfian (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to analyze the influence of attitudes, subjective norms, behavioral control, and maslahah on the intention to consume halal food and their implications for consumer behavior. Currently, the consumption of halal products in Indonesia continues to increase yearly, including in the province of West Sumatra, which has a majority Muslim community. For this reason, it is necessary to conduct research related to the consumption behavior of a consumer because the research results can affect economic growth. The distinguishes this research from previous research is the modification of TPB by adding the Maslahah variable. This study uses Islamic consumption theory, Islamic consumer behavior theory, and the Theory of Planned Behavior. This study uses survey data by distributing questionnaires to 100 respondents. Hypothesis testing uses SEM analysis with Smart PLS 4.0 software. The results of the hypothesis testing show that the attitude variable has no significant effect on intention. In contrast, the variables of subjective norm, behavioral control, and maslahah have a significant effect on consumption intention. The consumption intention variable also has a positive and significant influence on the consumption behavior of halal food among Muslim students in Padang city. Based on the results of the research, the implications of this research are the need for an understanding of religion to form a good attitude in carrying out consumption activities to avoid harm, besides that community cooperation, especially public figures, and scholars provides an example and encourages the community to carry out halal and good consumption. Keywords: Consumer Behavior, Islamic Consumption, Halal Food, Maslahah